Class underground, class aboveground: Zonguldak mineworkers and their unions - Kaya, Yasin. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This research is on the objective and subjective determinants of the Zonguldak mineworkers’ and their union’s power. It has three parts: First, it studies the effect of the structural and institutional forces functioning in global and national scale on the workplace and marketplace power of miners in the local context of Zonguldak. For this purpose, the evolution of the state-capital relations is studied through historical lenses with a specific emphasis on post-1980 era. Second, it inquires the mineworkers’ union’s organizational structure and strategies to analyze the grounds of mineworkers’ associational power. For this reason, it analyzes the historical development the union’s relation to its member base, the legal universe, TÜRK-İŞ and inter-party relations in Turkey. Third, it looks into the mineworkers’ perceptions questioning how they make meaning of the structural, institutional and ideological dynamics taking place in global, national and local levels that effect on their union and themselves; and how they conceptualize possible responses to such dynamics. Through this, it reflects on how mineworkers perceptions inform and be informed by the capacity of their union. The ultimate aim of this study is to underscore the necessity of dual approach to working class. It recommends studying it as an objective structural position in the relations of production that is shaped in its interplay with the state and capital; and as a subjective cultural formation that is constituted by workers’ experiences, practices, attitudes, beliefs, consciousnesses, and perceptions.
Keywords: Coal miners -- Turkey -- Zonguldak.